New publishing and scientific communication ways: Electronic edition, digital educational resources - Cordón-Garcia, José A. (2017)
The scientific edition has undergone a profound transformation in the last years. The production of research results from big data techniques, the accessibility to them through open access systems and repositories, the appearance of digital tools for editing and organization of content, etc. are some of the elements that have introduced changes in the systems of scientific communication. This Track analyzes some of the problems posed by these movements by providing models and solutions for them